From GSM to LTE-Advanced Pro and 5G an introduction to mobile networks and mobile broadband - Sauter, Martin (Hoboken, New Jersey Wiley Professional, Reference & Trade, 2021)
'From GSM to LTE-Advanced Pro and 5G: an introduction to mobile networks and mobile broadband' provides technical descriptions of the various wireless technologies currently in use. It explains the rationales behind their differing mechanisms and implementations while exploring the advantages and limitations of each technology. Special focus is put on the practical implementation and design assumptions, and the performance and capacity of each system. This welcome fourth edition responds to the ever-evolving systems of modern mobile networks, including 5G New Radio.
Electronic reproduction
Keywords: 5G mobile communication systems; Global system for mobile communications; Long-Term Evolution (Telecommunications).; Mobile communication systems